Praktek Personal Hygiene Menstruasi (Studi Kasus Santri Pesantren Al-Islam Gorontalo) - Lintje Boekoeose; Lia Amalia; Rifka Reflinawati Hamzah Paris; Yasir Mokodompis (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2022)
One of the risk factors for the reproductive tract is poor menstrual hygiene. Where hygiene during menstruation such as changing sanitary napkins and cleaning the feminine area after urinating is often neglected by teenagers. Personal hygiene during menstruation is personal hygiene in an effort to maintain, maintain and improve hygiene and health for physical and psychological well-being through the implementation of hygiene measures performed during menstruation. The purpose of the study was to determine the factors that influence the practice of personal hygiene in female students. The study used an analytical survey method with a cross sectional study design. The population is all students of class VII and VIII as many as 160 people with the determination of the sample using purposive sampling technique obtained 115 respondents. Data analysis using Chi-Square test. The results of the Chi-Square test are the level of knowledge, p-value = 0.005 <0.05, attitude of young women p-value = 0.017 <0.05, source of information p-value = 0.024 <0.05, family support p-value = 0.029 < 0.05. So that these four factors indicate that there is an influence on the practice of menstrual personal hygiene at the Al-Islam Islamic Boarding School, Gorontalo Regency. Suggestions or recommendations for schools to add lessons and curriculum as well as counseling for students about personal hygiene during menstruation.Salah satu faktor risiko saluran reproduksi ialah hygiene menstruasi yang buruk. Dimana kebersihan saat menstruasi seperti mengganti pembalut dan membersihkan daerah kewanitaan setelah buang air kecil sering sekali diabaikan oleh remaja. Personal hygiene selama menstruasi adalah kebersihan perorangan dalam usaha memelihara, mempertahankan serta memperbaiki kebersihan dan kesehatan untuk kesejahteraan fisik maupun psikologis melalui implementasi tindakan hygiene yang dilakukan saat menstruasi. Tujuan penelitian untuk mengetahui faktor yang mempengaruhi praktek personal hygiene pada santriwati. Penelitian menggunakan metode survey analitik dengan rancangan cross sectional study. Populasi adalah seluruh santriwati kelas VII dan VIII sebanyak 160 orang dengan penentuan sampel menggunakan teknik purposive sampling didapatkan 115 responden. Analisis data menggunakan uji Chi-Square. Hasil Uji Chi-Square yaitu tingkat pengetahuan p-value = 0,005 < 0,05, sikap remaja putri p-value = 0,017 < 0,05, sumber informasi p-value = 0,024 < 0,05, dukungan keluarga p-value = 0,029 < 0,05. Sehingga empat faktor tersebut menunjukkan terdapat pengaruh terhadap praktek personal hygiene menstruasi di Pesantren Al-Islam Kabupaten Gorontalo. Saran atau rekomendasi bagi sekolah agar menambahkan pelajaran dan kurikulum serta penyuluhan bagi siswi tentang personal hygiene saat menstruasi.